Políticas públicas de formação de professores: o estágio supervisionado do curso de pedagogia da Universidade Federal de Santa Maria no contexto do Covid-19 - Branco, Lílian Soares Alves (2024)
This thesis investigates the impacts of the COVID-19 pandemic on initial teacher education, focusing on the supervised internships of the in-person Pedagogy courses at the Federal University of Santa Maria (UFSM). Embedded in the research line Educational Public Policies, Educational Practices, and Their Interfaces, the study addresses the challenges of pedagogical praxis in times of crisis.The central question is: How did the COVID-19 pandemic interfere with the pedagogical praxis developed in the curricular internships of students in the in-person Pedagogy Licentiate courses at UFSM? The general objective is to understand the effects of the changes imposed by the pandemic on the pedagogical practices of supervised internships, considering how these transformations impacted teaching praxis and the formative development of future teachers. Using a qualitative and exploratory methodology, the study is structured as a case study. Data were collected through an online questionnaire, and the final research sample consisted of seven respondents: four graduate students and three internship supervising professors. Content analysis, based on Bardin (2011), allowed for the identification of emerging categories. The theoretical framework is supported by authors such as Freire (1996), Tardif (2014), Schön (1983), and Ball and Bowe (1992), among others. Additionally, normative documents such as Law nº. 9.394/96 (Brazil, 1996), CNE/CP Opinion nº. 5/2020 (Brazil, 2020d), MEC Ordinance nº. 544/2020 (Brazil, 2020f), and institutional documents from UFSM were considered.The thesis examines supervised internships both in the in-person context and in the adaptations made during Emergency Remote Teaching (ERE), highlighting the theoretical and legal foundations that underpin initial teacher education and the impacts of these emergency changes on pedagogical praxis.The results reveal that the pandemic brought significant challenges to supervised internships, especially in the process of articulating theory and practice, which became even more complex due to technological limitations and the impact on students who did not participate in teacher training programs such as PIBID and PRP. The thesis argues that pedagogical praxis was profoundly redefined during the pandemic, standing out as a dynamic process of action and reflection concerning education. This study contributes to the debate on the restructuring of initial teacher education, emphasizing the importance of integrating pedagogical innovations, expanding access to practical experience programs, and promoting curricula that prepare future teachers to deal with adverse and constantly changing realities.